Tindak Pidana Dugaan Pemalsuan Akta Otentik Dan Keadaan Perlindungan Hukum Notaris - Amara Diva Abigail (Officium Notarium, 2022)
This study aims to examine the criminal act of alleged forgery of authentic deeds and the state of notary legal protection. An authentic deed is a formal truth that concerns any matter and is notified by the parties to the Notary which is then contained in a deed. However, in practice, a good number od unlawful acts have occurred because the public has provided information that is not in accordance with the authentic deeds and providing fake documents. Hence the Notary can be harmed in this case. This study has a formulation of the problem, namely how is the condition of the notary's legal protection against the alleged crime of forgery of deed? The research method used is Juridical Empirical with statutory approach. The results of the study conclude that there is a state of legal protection for alleged criminal acts if the violation committed is still in the position of a notary, not a personal violation. Legal protection for notaries is carried out by the Notary Honorary Council under the Law on Notary Positions. Criminal acts committed by a notary also violate the provisions of the Criminal Code and can be tried by investigators through procedures approved by the Notary Ethics Council.Key Word: Notary, Crime, Legal Protection AbstrakPenelitian ini bertujuan mengkaji tindak pidana dugaan pemalsuan akta otentik dan keadaan perlindungan hukum notaris. Akta otentik merupakan kebenaran formil yang menyangkut hal apapun dan diberitahukan oleh para pihak kepada notaris yang kemudian dimuat dalam suatu akta. Namun dalam praktiknya, banyak perbuatan melawan hukum yang terjadi karena pihak publik memberikan keterangan yang tidak sesuai dengan akta otentik serta pembuatan dokumen palsu. Sehingga dalam hal ini pihak notaris dapat dirugikan. Penelitian ini memiliki rumusan masalah yaitu bagaimana keadaan perlindungan hukum notaris terhadap dugaan tindak pidana pemalsuan akta. Metode penelitian yang digunakan adalah Yuridis Empiris dengan pendekatan perundang-undangan. Hasil penelitian menyimpulakn bahwa terdapat keadaan perlindungan hukum atas dugaan tindak pidana berlaku jika pelanggaran yang dilakukan masih dalam jabatan notaris, bukan pelanggaran pribadi. Perlindungan hukum terhadap notaris dilakukan oleh Majelis Kehormatan Notaris dibawah Undang-Undang Jabatan Notaris. Tindak pidana yang dilakukan notaris juga menyalahi aturan KUHPidana dan bisa diadili oleh penyidik melalui prosedur yang disetujui Majelis Kehormatan Notaris.Kata-kata Kunci: Notaris, Tindak Pidana, Perlindungan Hukum